Deletion of Hnrnpk Gene Causes Infertility in Male Mice by Disrupting Spermatogenesis - Haixia Xu; Jiahua Guo; Wei Wu; Qiu Han; Yueru Huang; Yaling Wang; Cencen Li; Xiaofang Cheng; Pengpeng Zhang; Yongjie Xu (Cells, 2022)
HnRNPK is a heterogeneous nuclear ribonucleoprotein (hnRNP) that has been firmly implicated in transcriptional and post-transcriptional regulation. However, the molecular mechanisms by which hnRNPK orchestrates transcriptional or post-transcriptional regulation are not well understood due to early embryonic lethality in homozygous knockout mice, especially in a tissue-specific context. Strikingly, in this study, we demonstrated that hnRNPK is strongly expressed in the mouse testis and mainly localizes to the nucleus in spermatogonia, spermatocytes, and round spermatids, suggesting an important role for hnRNPK in spermatogenesis. Using a male germ cell-specific hnRNPK-depleted mouse model, we found that it is critical for testicular development and male fertility. The initiation of meiosis of following spermatogenesis was not affected in Hnrnpk cKO mice, while most germ cells were arrested at the pachytene stage of the meiosis and no mature sperm were detected in epididymides. The further RNA-seq analysis of Hnrnpk cKO mice testis revealed that the deletion of hnRNPK disturbed the expression of genes involved in male reproductive development, among which the meiosis genes were significantly affected, and Hnrnpk cKO spermatocytes failed to complete the meiotic prophase. Together, these results identify hnRNPK as an essential regulator of spermatogenesis and male fertility.